Associação de comorbidades clínico-laboratoriais nas alterações histopatológicas observadas em biópsias hepáticas de pacientes portadores de hepatite C crônica - Gustavo Henrique De Puy e Souza (2017)
HCV is a relevant cause of chronic hepatitis, cirrhosis, hepatocellular carcinoma and is the leading cause of liver transplant worldwide. Additionally, several extrahepatic manifestations are also reported in chronic hepatitis C (CHC) subjects. Several evidences have been demonstrated that HCV infection is associated with dyslipidaemia as there is a strong interaction between the HCV life cycle and intracellular lipids metabolism. In this study, we hypothesized that host factors including clinical comorbidities and lifestyle data would have an influence on liver histopathological features. In this cross-sectional study conducted at the Viral Hepatitis Outpatient Clinics University Hospital, we reviewed liver biopsies of 85 patients to classify each one based on the METAVIR criteria and to evaluate the presence of inflammatory cells types, quantities and lobular distribution. These histopathological features were correlated clinical comorbidities such as diabetes mellitus (DM), hypertension (HTN) and lipid profile in patients with CHC. Histological findings in the liver specimens of CHC patients with and without HDL cholesterol ≥ 55 mg/dl were compared. Among the histological variables tested during univariate analysis, liver necrosis, periportal inflammatory infiltrate, periportal lymphocytes and lobular inflammatory infiltrate were found to be associated with HDL cholesterol < 55 mg/dl in CHC patients. Overweight, DM, HTN were associated with hepatic necroinflammatory activity. Increased levels of ALT, AST, bilirubin, triglycerides and decreased levels of HDL cholesterol were associated with hepatic necroinflammatory activity as well. In multivariate analysis HDL cholesterol serum levels had an inverse association with fibrosis stage (OR 0,96, IC 0,93-0,99, p = 0,04) and the presence of necroinflammatory activity (OR 0,95, IC 0,92-0,99, p = 0,007). The correlation remains when comparing with the degree of hepatic necroinflammatory activity (p = 0.007). Recent studies are suggesting HDL to be a biomarker of inflammatory conditions, however measuring HDL cholesterol levels may not accurately predict the composition, functionality, and anti-inflammatory properties of HDL. In our study, HDL cholesterol serum level ≥ 55 mg/dl had a protective effect in CHC outcome. Further studies are necessary to better understand this relationship